Personal Branding Strategy through TikTok in Increasing Interest in Purchasing MSME Products in Medan City - Humairoh, Jihan; Tantia, Myrna Dwi; Regen (JUMEBIN : Journal of Management, Economics, Business, and Investment, 2025)
The development of social media has driven the transformation of MSME marketing strategies, including the use of TikTok as an interactive, content-based digital promotion platform. This study aims to analyze the role of personal branding strategies through TikTok in increasing interest in purchasing MSME products in Medan City. The approach used is participatory assistance with stages of needs identification, training and content creation practice, implementation of personal branding strategies, and evaluation of the impact on consumer response. The research subjects are SME actors who actively use TikTok as a promotional medium. The results of the study show that the consistent, authentic, and communicative application of personal branding can increase audience engagement, strengthen the credibility of business actors, and encourage an increase in consumer purchasing interest. The change in communication patterns from one-way promotion to two-way interaction through the comment and live streaming features has proven to strengthen the emotional closeness between MSME actors and consumers. In addition, the increase in the digital literacy of participants also supports the optimization of TikTok features in reaching a wider market. This study concludes that personal branding is an effective digital marketing strategy in strengthening the competitiveness of MSMEs in the creative economy era. These findings have practical implications for MSME players to integrate personal identity into digital marketing strategies, as well as enriching social media-based entrepreneurship studies at the local level.